2012
DOI: 10.1186/cc11839
|View full text |Cite
|
Sign up to set email alerts
|

Empirical use of fluoroquinolones improves the survival of critically ill patients with tuberculosis mimicking severe pneumonia

Abstract: IntroductionEmpirical use of fluoroquinolones may delay the initiation of appropriate therapy for tuberculosis (TB). This study aimed to evaluate the impact of empirical fluoroquinolone use on the survival of patients with pulmonary TB that mimicked severe community-acquired pneumonia (CAP) requiring intensive care.MethodsPatients aged >18 years with culture-confirmed pulmonary TB who presented as severe CAP and were admitted to the ICU were divided into fluoroquinolone (FQ) and nonfluoroquinolone (non-FQ) gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…There are several reports of the impact of FQ exposure prior to TB diagnosis on various clinical outcomes in patients with TB (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). However, to our knowledge, this is the first study evaluating the impact of FQ use prior to TB diagnosis on clinical outcomes in immunocompromised patients with TB.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…There are several reports of the impact of FQ exposure prior to TB diagnosis on various clinical outcomes in patients with TB (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). However, to our knowledge, this is the first study evaluating the impact of FQ use prior to TB diagnosis on clinical outcomes in immunocompromised patients with TB.…”
Section: Discussionmentioning
confidence: 47%
“…However, a recent study in Taiwan demonstrated that empirical use of FQ improved the survival rate of critically ill patients with TB that mimicked severe pneumonia, without causing treatment delay and FQ resistance (27). In that study, significantly more patients in the non-FQ group (27%) than in the FQ group (9%) died before anti-TB therapy was started.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…21 Other documented risk factors for mortality include nosocomial pneumonia, multi-organ failure, TB destroyed lung, an APACHE II score >20 and duration of symptoms >4 weeks. 11,22,23…”
Section: Resultsmentioning
confidence: 99%
“…rifampicin+moxifloxacin+amikacin) may be administered. Empirical intravenous fluoroquinolone use improved the survival of critically ill patients admitted for pulmonary TB [11]. Several studies have reported that higher than usual doses of anti-TB drugs (e.g.…”
Section: A Novel Approach To Anti-tb Treatment In Critically Ill Patimentioning
confidence: 99%